FORMULASI PERBANDINGAN LIMBAH KULIT KAYU AKASIA (ACASIA MANGIUM) DAN TEPUNG TAPIOKA SEBAGAI BAHAN BAKU PEMBUATAN BIO BRIKET - Ruby Afrizon; Anwar Kasim; Dewi Arziyah (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2023)
This study aims to determine the effect of the concentration of acacia bark and tapioca flour on the characteristics of acacia bark biobriquettes. This research was conducted at the Laboratory for Analysis of Physical Properties of Materials and Products, Agricultural Industrial Technology, Dharma Andalas University, Padang. The design used in this study was a completely randomized design (CRD) with a comparison of the percentage of adhesive concentration, namely: A = 0%, B = 5%, C = 10%, D = 15%, E = 20% with 3 replications. Observations from each treatment were analyzed by ANOVA. If it is significantly different, then continue using the DNMRT follow-up test at the 5% level. The research was carried out in two stages, the first stage was the manufacture of biobriquettes with a comparison of the percentage of adhesive concentration and chemical analysis testing of the biobriquettes was carried out. The results showed that the comparison of the percentage of adhesive concentration had a significant effect on moisture content, ash content, density test, calorific value and burning rate. The results of testing on biobriquettes obtained treatment E. with the addition of 20% adhesive.